Zn(OTf)2-mediated CH activation: An expeditious and solvent-free synthesis of aryl/alkyl substituted quinolines. Issue 51 (21st December 2016) - Sarode, Prashant B.; Bahekar, Sandeep P.; Chandak, Hemant S.
Graphical abstract: Highlights: Zn(OTf)2 -mediated CH activation. Synthesis of aryl/alkyl substituted quinolines. Less accessible alkyl substituted quinolone can be prepared. Pseudo three-component Povarov reaction of anilines and butanal afforded 2, 3-dialkyl quinolines. Robust solvent-free process avoids the use of precious metals and hazardous solvents. Abstract: Zinc(II) triflate catalyzed three-component coupling reactions of alkynes, amines and aldehydes leading to the formation of aryl/alkyl substituted quinolines has been described. Notably, the reaction proceeded efficiently and effectively without the use of ligand, co-catalyst, solvent or inert atmosphere. This robust solvent-free process operates under an ambient atmosphere and avoids the use of precious metals, hazardous solvents and harsh reaction conditions. This atom economic process eliminates the waste generated in the multistep synthesis. Additionally, a pseudo three-component Povarov reaction of amines and butanal proceeds under the same green conditions enabling the formation of 2, 3-dialkyl quinolines.